(untitled) (Journal of the College of Education for Women, 2025)
Human trafficking is widely recognized as a major challenge of the 21st century. The United Nations (UN), as the primary deliberative, policy-making, and coordinating entity, plays a crucial role in defining the collective vision for effectively combating human trafficking. Consequently, the UN publishes reports on human trafficking to provide an in-depth analysis of trafficking trends, information on victims, and prosecutions related to this crime. Due to the sensitivity of this issue, vagueness is sometimes employed in these reports. Vagueness is a common phenomenon encompassing expressions inherently lacking in precision and utilized for various interactional and social purposes. This paper aims to semantically investigate and pragmatically analyze the use of vagueness in these reports. The study contributes to the fields of semantics and pragmatics by examining how vague expressions function in discourse, thereby enriching linguistic theory and its applications. To achieve this aim, the researchers have adopted Channell’s (2000) seminal work on vagueness on the semantic level and Levinson’s (2000) Neo-Gricean approach on the pragmatic level. Four UN reports on human trafficking are purposefully selected and analysed qualitatively. The paper has come to certain conclusions, among which all the types of vague expressions identified in Channel’s (2000) taxonomy of vagueness have been found in UN reports on human trafficking. Vagueness is often used to omit less important information, avoid conveying incorrect information, and attract attention. Vagueness in the UN reports on human trafficking serves several functions, including vague language helps to establish effective communication through concise language, promoting interactive mutual understanding between the interlocutors.